Analisis Beban Mental dan Kelelahan Siswa Dalam Pembelajaran Daring Pada Masa Pandemi Covid 19 - Choirul Bariyah; Tri Utami Siahaan (Prosiding, 2022)
Based on the results of observations made on students of SMA Negeri 1 Torgamba, it was obtained that students experienced a number of obstacles in participating in online learning. These obstacles include the internet network, difficulty to understanding the material being taught, discomfort in the learning environment. These difficulties trigger the emergence of indications of students experiencing fatigue both physically and psychologically. Complaints such as feeling tired, eye pain, boredom, confusion, sleepy, headache. The study was conducted to measure the level of fatigue and mental load of class XII students. Fatigue level was measured by the Swedish Occupational Fatigue Inventory (SOFI) method and mental load was measured by the National Aeronautics Administration Task Load Index (NASA TLX). Based on the results of data processing with SOFI, it is known that the highest dimension of student fatigue during online learning is lack of energy with a score of 5.013 for the science class and 4,495 for the social studies class. The students mental workload for each class has the largest proportion in the very high category, namely 75% for the science class and 52% for the social science class. Based on the Mann Whitney test, it is known that there is a difference between the level of mental load and fatigue of students in science and social studies class